Response: Physical Education Learning Assignment Amid the Covid-19 Pandemic - Oki Candra; Wahyudi Wahyudi; Tri Prasetyo (Inspiree)
The  purpose  of  the study. The purpose of this study was to find out how deep the response of students to the assignment assigned by the health physical education teacher in determining the number of respondents when the teacher gave physical education assignments.